Comparison of methodologies in determining bone marrow fat percentage under different environmental conditions: assessing a tool for ruminant welfare investigations. (January 2017) - Murden, David; Hunnam, Jaimie; De Groef, Bert; Rawlin, Grant; McCowan, Christina
The use of bone marrow fat percentage has been recommended in assessing body condition at the time of death in wild and domestic ruminants, but few studies have looked at the effects of time and exposure on animal bone marrow. We investigated the utility of bone marrow fat extraction as a tool for establishing antemortem body condition in postmortem specimens from sheep and cattle, particularly after exposure to high heat, and compared different techniques of fat extraction for this purpose. Femora were collected from healthy and "skinny" sheep and cattle. The bones were either frozen or subjected to 40°C heat; heated bones were either wrapped in plastic to minimize desiccation or were left unwrapped. Marrow fat percentage was determined at different time intervals by oven-drying, or by solvent extraction using hexane in manual equipment or a Soxhlet apparatus. Extraction was performed, where possible, on both wet and dried tissue. Multiple samples were tested from each bone. Bone marrow fat analysis using a manual, hexane-based extraction technique was found to be a moderately sensitive method of assessing antemortem body condition of cattle up to 6 d after death. Multiple replicates should be analyzed where possible. Samples from "skinny" sheep showed a different response to heat from those of "healthy" sheep; "skinny" samples were so reduced in quantity by day 6 (the first sampling day) that no individual testing could be performed. Further work is required to understand the response of sheep marrow.